Reading Roman declamation : the declamations ascribed to Quintilian - Dinter, Martin T.; Guérin, Charles, 1978-; Martinho dos Santos, Marcos (Beiträge zur Altertumskunde,, 2016)
As a genre situated at the crossroad of rhetoric and fiction, declamatio offers the freedom to experiment with new forms of discourse. Placing the literariness of declamatio into the spotlight, this volumeshowcases declamation as a realm of genuine literary creation with its own theoretical underpinning, literary technique and generic conventions. Focusing on the oeuvre of (Ps)Quintilian, this volumedemonstrates that these texts constitute a genre on their own, the rhetorical and literary framework of which remains not yet fully mapped.It is of interest to students and scholars of Rhetoric and Roman Literature.